Analisis Implementasi PRODIS dalam Mendukung Efektivitas Pelaporan Kegiatan On-Farm Budidaya Tebu - Siregar, Nydia Pratiwi; Nainggolan, Saidin (Universitas Medan Area, 2026)
This study analyses the implementation of the Production Information System (PRODIS) in improving the effectiveness of reporting on-farm sugarcane cultivation activities at the Kwala Madu MKSO plantation of PT Sinergi Gula Nusantara. Effectiveness is measured in terms of time, accuracy, consistency and uniformity of data before and after the implementation of the system. Data were collected through questionnaires, interviews, and documentation, and analysed using a descriptive approach and the Wilcoxon Signed Rank Test. The results show that PRODIS significantly speeds up reporting, improves data accuracy, and maintains consistency of information between work units. The digitisation of reporting enables more integrated data management and supports more effective managerial decision-making. These findings confirm the important role of digital information systems in improving the effectiveness of on-farm activity reporting at the plantation level.